Development and Thinking of Classical Islamic Pharmacy Towards a Progressive and Sustainable Pharmacy - Intan Trisakti; Muhammad Imam Riswanto; Rosi Hayyu; Hanif Fibiana Asyhari; Muthoifin; Hanifah Ridha Azzahra; Muhammad Reza Aziz Prasetya; Ahmad Alfarobi Jauharul Ilmi; Ariq Fadhlur Cahyanto9; Ishmah Afiyah (Walidem Institute and Publishing, 2023)
The purpose of this study is to determine the existence of pharmaceutical science inseparable from its development history which is a long process of growth and development of pharmaceutical science. The method used is library research. The results of the study showed that the development of Islamic pharmacy went through four phases, namely (first phase, second phase, third phase, and fourth phase) and in each of these phases Muslim scientists made a significant contribution to the development of pharmaceutical science. Pharmaceutical services today have been growing in addition to being product-oriented, also patient-oriented.